KERAGAAN FENOTIP MUTAN JAGUNG VARIETAS MADURA (Zea mays sp.) GENERASI PERTAMA - Visto Renardi Kusumawardana; Makhziah Makhziah; Ida Retno Moeljani (UPN VETERAN JAWA TIMUR, 2018)
Aim of the research is to know the performance and heritability value of ten from first generation of Madura mutant maize varieties (Zea mays sp.). It was conducted at Agriculture Faculty, UPN “Veteran” Jawa Timur on July-September 2017. Randomized Block Design method was used with 1 factor that consists of 10 lines first generation Madura mutant maize varieties and repeated 3 times. Data was analyzed used ANOVA (Analysis of Variance) and the Honestly Significant Difference Test 5%. As the results, MM-100-3-023 has the best performance among the ten first generation of Madura mutant maize varieties for plant height, the number of leaves, seed weight, 100-grain weight, number of seeds, cob weight and dry weight of the plant, and the heritability showed the low, medium and high range.